Deep sequencing of amplified Prasinovirus and host green algal genes from an Indian Ocean transect reveals interacting trophic dependencies and new genotypes. Issue 6 (December 2015) - Clerissi, Camille; Desdevises, Yves; Romac, Sarah; Audic, Stéphane; de Vargas, Colomban; Acinas, Silvia G; Casotti, Raffaella; Poulain, Julie; Wincker, Patrick; Hingamp, Pascal; Ogata, Hiroyuki; Grimsley, Nigel
Summary: High‐throughput sequencing of P rasinovirus DNA polymerase and host green algal (Mamiellophyceae) ribosomal RNA genes was used to analyse the diversity and distribution of these taxa over a ∼10 000 km latitudinal section of the Indian Ocean. New viral and host groups were identified among the different trophic conditions observed, and highlighted that although unknown prasinoviruses are diverse, the cosmopolitan algal genera B athycoccus, M icromonas and O streococcus represent a large proportion of the host diversity. While P rasinovirus communities were correlated to both the geography and the environment, host communities were not, perhaps because the genetic marker used lacked sufficient resolution. Nevertheless, analysis of single environmental variables showed that eutrophic conditions strongly influence the distributions of both hosts and viruses. Moreover, these communities were not correlated, in their composition or specific richness. These observations could result from antagonistic dynamics, such as that illustrated in a prey–predator model, and/or because hosts might be under a complex set of selective pressures. Both of these reasons must be considered to interpret environmental surveys of viruses and hosts, because covariation does not always imply interaction.